A Study of Girls' Adjustment Studying In Co-Educational Degree Colleges and Girls Degree Colleges: Challenges faced by girls in co-educational and single-gender degree colleges (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Man is a socialcreature. He has ability to adjust in the society and to work according to lawsof society. He has to mould his behaviour and circumstances according todifferent situations and thereby he accommodates himself in his environment.But sometimes, he has to face many problems while dealing with varioussituations encountered by him in his life.